2002
DOI: 10.1148/radiol.2251011029
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Lobular Carcinoma of the Breast: Mammographic Characteristics and Computer-aided Detection

Abstract: Spiculated masses and architectural distortions are the predominant appearances of invasive lobular carcinoma, and a computer-aided detection system correctly marked a high percentage of invasive lobular carcinoma lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
3
2

Year Published

2005
2005
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(45 citation statements)
references
References 16 publications
2
38
3
2
Order By: Relevance
“…Similarly, Krecke and Gisvold reported false-negative mammography rates of 57% for D4, 29% for D3 and 9% for D2 breast densities (10). ILC appearing as a mass lesion mammographically may have a spiculated appearance (28,29). In addition to an ill-defined opacity, parenchymal asymmetry and architectural distortion are the other mammographical findings of ILC (17,28,29).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Similarly, Krecke and Gisvold reported false-negative mammography rates of 57% for D4, 29% for D3 and 9% for D2 breast densities (10). ILC appearing as a mass lesion mammographically may have a spiculated appearance (28,29). In addition to an ill-defined opacity, parenchymal asymmetry and architectural distortion are the other mammographical findings of ILC (17,28,29).…”
Section: Discussionmentioning
confidence: 95%
“…ILC appearing as a mass lesion mammographically may have a spiculated appearance (28,29). In addition to an ill-defined opacity, parenchymal asymmetry and architectural distortion are the other mammographical findings of ILC (17,28,29). Additionally, ILC may be invisible on mammograms because the density of ILC tends to be relatively low, similar to that of normal breast parenchyma, which may be the result of the relative paucity of a desmoplastic response (30).…”
Section: Discussionmentioning
confidence: 99%
“…This so-called 'Indian file' pattern of infiltration causes a modest disruption of the underlying anatomic structures and generates little surrounding desmoplastic stromal reaction (Dixon et al 1982). Clinical examination of patients with ILC can be complicated because of vague findings, such as thickening or induration, which are often the only clinical signs, particularly in early disease (Evans et al 2002).…”
Section: Diagnosis Of Invasive Lobular Cancermentioning
confidence: 99%
“…The sensitivity of detecting ILC has been reported to be as low as 57-76% for Mx (Le Gal et al 1992, Evans et al 2002, while false negative rates at Mx have been observed to range from 8 to 24% (Helvie et al 1993, Krecke & Gisvold 1993. In the study by Krecke & Gisvold (1993) the mammograms of patients with ILC initially classified as normal (i.e.…”
Section: Mammographymentioning
confidence: 99%
See 1 more Smart Citation